Analysis of inhomogeneous local distribution of potential induced degradation at a rooftop photovoltaic installation. Issue 10 (24th August 2017) - Buerhop, Claudia; Pickel, Tobias; Patel, Tirth; Fecher, Frank W.; Zetzmann, Cornelia; Camus, Christian; Hauch, Jens; Brabec, Christoph J.
Abstract : Potential induced degradation (PID) of photovoltaic (PV) modules is one of the frequently observed failures in PV installations nowadays. This study investigates the inhomogeneous and complex PID generation on rooftop installations on industrial buildings as well as its impact on the module performance. The PID development is exemplarily presented for a 314kWp PV‐plant installed in the Atlantic coastal climate. Due to the complex plant geometry and resulting irradiation situation the existence of PID could not be identified based on the annual yield data. By Infrared imaging PID was clearly identified. Evaluating historic monitoring data, the impact of PID on the string and plant performance could be quantified. A linear correlation between the defect ratio and the performance rate as well as the degradation loss rate could be formulated.